Cause-and-effect relationship of yield and its components under cold-stress condition in rice (Oryza sativa) - GUPTA, J C; KATOCH, P C; KAUSHIK, R P; SHARMA, S L (The Indian Journal of Agricultural Sciences, 2013)
Rice (Oryza sativa L,) genotypes (38) from diverse origin were studied for correlation and path-coefficient analysisunder cold-stress condition for grain yield, using 9 characters, Grain yield was positively correlated with 1 000-grainweight and negatively with sterility (%) and plant'height. Panicle length, panicle density and sterility(%) were themain component characters affecting yield directly, High and positive indirect effects were contributed by 1 000-grainweight and days to flowering through grains/panicle and panicle length respectively, The combined results of correlationsand path coefficients indicated that 1 000-grain weight and days to flowering through grains/panicle and panicle lengthrespectively. The combined results of correlations and path coefficients indicated that 1 000-grain weight, spikeletfertility and short pIant height have maximum effect on selection for improvement in grain yield of rice under coldstresscondition.